Isolation and screening of kojic acid producing isolate of Aspergillus oryzae potentially applicable for production from sugarcane molasses - Rasmey, Abdel-hamied; Basha, Aya (International Journal of Biological Research, 2016)
Kojic acid is an organic acid produced as secondary metabolite by different fungi specially Aspergillus species. Isolation of a novel fungal strain potential for kojic acid production from agro-industrial wastes was the main purpose of the present study. Kojic acid was estimated in the current investigation colorimetric by 2,6-dichlorophenolindophenol (DCIP). A total of 43 fungal isolates belonging to seven species of Aspergillus recovered from stored wheat grains and dust air were screened for their ability to produce kojic acid. Ten isolates of them belonging to A. oryzae and A. flavus var. columnaris produced high concentrations (16.818 ± 0.006 - 43.917 ± 0.389 g/l) of kojic acid from glucose. The secondary screening of these ten isolates for kojic acid production from glucose, sucrose, starch, maltose and cellulose as different carbon sources resulted that A. oryzae 124A was the highly producer on glucose and sucrose recording 44.189 ± 0.079 and 32.135 ± 0.298 g/l, respectively. A. oryzae 124A produced 15.022 ± 0.017 g/l of kojic acid from the pretreated semisynthetic sugarcane molasses. The maximum concentration (29.431 ± 0.001 g/l) of kojic acid production by A. oryzae 124A from sugarcane molasses was obtained when the fungus grown on 5 % sugarcane molasses adjusted at pH 3.5 and incubated at 28∘C for 19 days. The recorded results suggested that A. oryzae 124A could be used as a promising candidate for utilization in kojic acid fermentation from sugarcane molasses on industrial scale.